Two major genes confer Ascochyta blight resistance in Lens orientalis - Ye, G.; McNeil, D.L.; Hill, G.D. (New Zealand Plant Protection, 2000)
Genetic mechanisms of resistance to Ascochyta blight from wild lentil (Lens orientalis) were studied using F3 families of a cross between the cultivar Titore of the cultivated lentil (Lens culinaris) and accession W 6 3261 of the wild lentil The simplest genetic model to adequately fit the data involved two genes one partially dominant gene with a larger effect (A) and one dominant gene with a less effect (B) which acted additively to confer resistance One copy of the resistance increasing allele of the A gene is not sufficient for a genotype to be resistant nor is one or two copies of the resistance increasing allele of the B gene alone When fitted to other published data this model was as good as or better than alternative models that have been proposed